Emergency Medical Services Streaming Enabled Evaluation In Trauma: The SEE-IT Feasibility RCT - Cath Taylor; Lucie Ollis; Richard Lyon; Julia Williams; Simon S Skene; Kate Bennett; Scott Munro; Craig Mortimer; Matthew Glover; Janet Holah; Jill Maben; Carin Magnusson; et al. (Health and Social Care Delivery Research)
Some text in this abstract and article has been reproduced from Taylor et al. (Taylor C, Ollis L, Lyon RM, Williams J, Skene SS, Bennett K, et al.; SEE-IT Trial Group. The SEE-IT Trial: emergency medical services Streaming Enabled Evaluation In Trauma: a feasibility randomised controlled trial. Scand J Trauma Resusc Emerg Med 2024;32:7). This is an Open Access article distributed in accordance with the terms of the Creative Commons Attribution (CC BY 4.0) license, which permits others to distribute, remix, adapt and build upon this work, for commercial use, provided the original work is properly cited. See: https://creativecommons.org/licenses/by/4.0/. The text below includes minor additions and formatting changes to the original text. Background The use of bystander video livestreaming from scene in emergency medical services is becoming increasingly common to inform decisions about the resources and support required. Possible benefits include clinical and financial gains, but evidence is sparse. We aimed to investigate the feasibility of conducting a definitive randomised controlled trial of its use in major trauma incidents. Objectives To obtain data required to design a subsequent randomised controlled trial. To test trial processes. To embed a process evaluation. Design A feasibility randomised controlled trial with embedded process and economic evaluations where working shifts (n = 62) in 6 trial weeks were randomised 1 : 1 to video livestreaming or standard care only; and two observational substudies: (1) assessment of acceptability in a diverse inner-city emergency medical service that routinely uses video livestreaming; and (2) assessment of staff well-being in an emergency medical service that does not use livestreaming (for comparison to the trial site). Qualitative data collection included observations (286 hours) and interviews with staff (n = 25) and bystander callers (n = 2). Setting A pre-hospital emergency medical service in South-East England, with follow-up in associated major trauma centres and trauma units; substudies in (1) London and (2) East of England emergency medical services. Participants (1) Patients involved in trauma incidents (n = 269); (2) bystander callers (n = 11); and (3) ambulance service staff (n = 67). Intervention Video livestreaming using GoodSAM’s Instant-On-Scene. Main outcome measures Progression to a definitive randomised controlled trial based on four pre-defined criteria and consideration of qualitative data: (1) ≥ 70% bystanders with smartphones agreeing and able to activate livestreaming; (2) ≥ 50% requests to activate livestreaming resulting in footage being viewed; (3) helicopter emergency medical services stand-down rate reducing by ≥ 10% due to livestreaming; and (4) no evidence of psychological harm to bystanders or staff caused by livestreaming. Results Sixty-two shifts were randomised, contributing 240 eligible incidents (132 control; 108 intervention). In a further three shifts, we randomised by individual call, which contributed four eligible incidents (two control; two intervention), thereby totalling 244 incidents involving 269 patients. Video livestreaming was successful in 53 incidents in the intervention arm. Patient recruitment (to access medical records to assess appropriateness of dispatch) and bystander recruitment (to measure potential harm) were both low (58/269, 22% of patients, 4/244, 2% of bystanders). Two progression criteria were met: (1) 86% of bystanders with smartphones agreed and were able to activate livestreaming; (2) 85% of requests to activate livestreaming resulted in viewed footage; and two were indeterminate due to insufficient data: (3) 2/6 (33%) stand-down due to livestreaming; and (4) no evidence of psychological harm from survey, observations or interviews. In substudy (i), dispatch staff reported that non/limited English language and older age may present barriers to video livestreaming. Limitations Poor recruitment of patients and bystanders limited assessment of appropriateness of dispatch decisions and potential psychological harm. Conclusions Video livestreaming is feasible to implement, acceptable to both bystanders and dispatchers, and may aid dispatch decision-making, but further assessment of benefits and harm is required. Future work Findings support the design and conduct of a future multicentre study taking account of different triage systems and dispatch personnel, potentially using an alternative to a randomised controlled trial due to rapid uptake of video livestreaming in this setting. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number NIHR130811. Plain language summary Why did we do this study? Witnesses to serious accidents who call 999 might sometimes give incomplete or incorrect information to the ambulance service about the patients’ injuries or scene, leading to delays getting the right help. The use of video livestreaming from a caller’s mobile phone might help improve the speed and accuracy of decisions made about which resources are needed (e.g. air ambulance or road ambulance). Before we can do a study to determine this, we needed to carry out a feasibility (pre) study to test the procedures and collect information needed to design a future study. This includes checking that 999 callers and staff are willing and able to use video livestreaming and that it does not cause additional stress compared to just talking on the phone. What did we do? We tested video livestreaming for serious incidents for 1 week per month (June–November 2022). During trial weeks, the dispatchers (people who decide which resources go where) either used livestreaming or not. This was a randomised trial, which meant that livestreaming was only attempted in half of the incidents. We could then compare the findings. We collected information from each incident, observed how livestreaming was used, and completed interviews and questionnaires with ambulance service staff and 999 callers. What did we find? Callers and ambulance service staff found video livestreaming easy to use and acceptable. We did not have enough data to conclude if it helped decide when the air ambulance should be sent, or if it caused additional stress to callers or ambulance staff, but findings supported doing a future study to answer these questions. What does this mean going forward? More research is needed to answer important questions about if and how video livestreaming can safely support decision-making about the help needed at accident scenes.